Effect of Plant Growth Promoting Rhizobacteria (PGPR) on Growth and Yield of Soybean - Paulus, Jeanne Martje; Tooy, Dedie (ITScience (Information Technology and Science), 2024)
This study aimed to (1) examine the effect of giving PGPR (Plant Growth Promoting Rhizobacteria) to increase soybean growth and production and (2) obtain the best dose of PGPR to increase soybean growth and production. The research was carried out in Tontalete Village, Kema District, North Minahasa Regency, North Sulawesi from June 2021 to October 2021. The field experiment was arranged in a Randomized Block Design (RBD). The treatment tested was the concentration of PGPR, which consisted of P0 = 0 ml/l (control), P1 = 5 ml/l, P2 = 10 ml/l, P3 = 15 ml/l, and P4 = 20 ml/l. The treatment was repeated three times, so there were 15 experimental units. Parameters observed were: plant height, number of branches, number of pods per plant, percentage of damaged pods per plant, the weight of 100 dry seeds, and seed yield/plot. The data were analyzed using the Analysis of Variance (ANOVA) and continued with the mean difference test using the Least Significant Difference Test (LSD) at the 5% level. The results showed that the application of PGPR affected the growth and yield of soybeans by increasing plant height, the number of pods per plant, and dry seed yield. The highest dry seed yield was achieved at PGPR concentrations of 10 ml/l and 15 ml/l, which were 1.34 g and 127.87 g, equivalent to 1.34 tons ha-1 and 1.28 tons ha-1, respectively.